Multifaceted roles of TAX1BP1 in autophagy. Issue 1 (2nd January 2023) - White, Jesse; Suklabaidya, Sujit; Vo, Mai Tram; Choi, Young Bong; Harhaj, Edward W.
ABSTRACT: TAX1BP1 is a selective macroautophagy/autophagy receptor that plays a central role in host defense to pathogens and in regulating the innate immune system. TAX1BP1 facilitates the xenophagic clearance of pathogenic bacteria such as Salmonella typhimurium and Mycobacterium tuberculosis and regulates TLR3 (toll-like receptor 3)-TLR4 and DDX58/RIG-I-like receptor (RLR) signaling by targeting TICAM1 and MAVS for autophagic degradation respectively. In addition to these canonical autophagy receptor functions, TAX1BP1 can also exert multiple accessory functions that influence the biogenesis and maturation of autophagosomes. In this review, we will discuss and integrate recent findings related to the autophagy function of TAX1BP1 and highlight outstanding questions regarding its functions in autophagy and regulation of innate immunity and host defense. Abbreviations: ATG: autophagy related; CALCOCO: calcium binding and coiled-coil domain; CC: coiled-coil; CHUK/IKKα: conserved helix-loop-helix ubiquitous kinase; CLIR: noncanonical LC3-interacting region; GABARAP: gamma-aminobutyric acid receptor associated protein; HTLV-1: human T-lymphotropic virus 1; IFN: interferon; IL1B/IL1β: interleukin 1 beta; LIR: LC3-interacting region; LPS: lipopolysaccharide; MAP1LC3/LC3: microtubule-associated protein 1 light chain 3; MAPK/JNK: mitogen-activated protein kinase; mATG8: mammalian Atg8 homolog; MAVS: mitochondrial antiviral signaling protein; MEF: mouse embryonic fibroblast; MTB: Mycobacterium tuberculosis ; MYD88: myeloid differentiation primary response gene 88; NBR1: NBR1, autophagy cargo receptor; NFKB/NF-κB: nuclear factor of kappa light polypeptide gene enhancer in B cells; OPTN: optineurin; Poly(I:C): polyinosinic:polycytidylic acid; PTM: post-translational modification; RB1CC1: RB1-inducible coiled-coil 1; RIPK: receptor (TNFRSF)-interacting serine-threonine kinase; RLR: DDX58/RIG-I-like receptor; RSV: respiratory syncytia virus; SKICH: SKIP carboxyl homology; SLR: SQSTM1 like receptor; SQSTM1: sequestosome 1; TAX1BP1: Tax1 (human T cell leukemia virus type I) binding protein 1; TBK1: TANK-binding kinase 1; TICAM1: toll-like receptor adaptor molecule 1; TLR: toll-like receptor; TNF: tumor necrosis factor; TNFAIP3: TNF alpha induced protein 3; TNFR: tumor necrosis factor receptor; TOM1: target of myb1 trafficking protein; TRAF: TNF receptor-associated factor; TRIM32: tripartite motif-containing 32; UBD: ubiquitin binding domain; ZF: zinc finger.